2021
DOI: 10.5210/spir.v2021i0.12192
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Self-Help—how Internet Users Protect Themselves Against Algorithmic Risks

Abstract: In today’s digitized society, internet users increasingly rely on online services that apply algorithmic selection, like for instance Google Search or the Facebook News Feed. The algorithms that are implemented in these services automatically select information sets and assign relevance to them. This entails societal risks such as privacy breaches, surveillance, manipulation, or overuse. One way for internet users to cope with these risks, is the use of self-help strategies such as deleting cookies or using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The interviews further reveal whether and how people react to a heightened sense of dataveillance with limiting their digital behavior. In addition to searching for information and expressing opinions, we identify further legitimate, Suggested Citation (APA): Kappeler, K., Festic, N., & Latzer, M. (2022, November) mundane behaviors in other life domains like participating in online dating and buying things online that are affected by a sense of dataveillance and have so far been neglected in literature on chilling effects. These results contribute to an empirically founded understanding of the nature of a sense of dataveillance and resulting chilling effects on digital behavior and thus advance research in this emerging field.…”
Section: Results and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews further reveal whether and how people react to a heightened sense of dataveillance with limiting their digital behavior. In addition to searching for information and expressing opinions, we identify further legitimate, Suggested Citation (APA): Kappeler, K., Festic, N., & Latzer, M. (2022, November) mundane behaviors in other life domains like participating in online dating and buying things online that are affected by a sense of dataveillance and have so far been neglected in literature on chilling effects. These results contribute to an empirically founded understanding of the nature of a sense of dataveillance and resulting chilling effects on digital behavior and thus advance research in this emerging field.…”
Section: Results and Contributionmentioning
confidence: 99%
“…Extant empirical research has confirmed that people are somewhat aware of dataveillance (e.g., Lupton, 2020) and that they limit their legitimate information and communication behavior in response to this perception (e.g., Marthews & Tucker, 2017;Penney, 2016;Stoycheff et al, 2019). However, the intricacies of these Suggested Citation (APA): Kappeler, K., Festic, N., & Latzer, M. (2022, November)…”
Section: Limited Existing Empirical Researchmentioning
confidence: 99%